An Unusual Cause of Lobulated Lung Mass - AH, Mohamed Faisal; HL, Tan; BYL, Andrea (IIUM Medical Journal Malaysia, 2016)
Eventration of the diaphragm is caused by weakened musculature of the diaphragm. This can occur in one or both hemidiaphragms. Symptoms may be minimal and it is usually detected incidentally on chest radiograph which would show an elevation of the diaphragm. We report and discuss a case of eventration of right diaphragm in a patient presented with a lobulated lung mass on chest radiograph.